Examining the mental health status of referees in the Turkish professional football league - Lima, Y.; Devran, S.; Öz, N. D.; Webb, T.; Bayraktar, B. (Science and Medicine in Football, 2023)
Objective: The purpose of the study was to evaluate the mental health (MH) status of referees who officiate in the Turkish professional football leagues. Method: An online survey was sent to all referees in the Turkish professional football leagues (n = 630) incorporating standardized scales assessing depression, anxiety, and stress. Results: A total of 433 referees participated in the study, yielding a response rate of 68.7%. Younger referees (18-27 years) reported higher depression (p = 0.01), anxiety (p < 0.01), and stress (p < 0.01) scores than older (>38 years) refereees. Depression, anxiety, and stress scores of single referees were higher compared to married referees (all p < 0.01). Lower-level referees reported higher depression (p < 0.01), anxiety (p = 0.01), and stress (p < 0.01) scores than their higher-level counterparts. Higher depression, anxiety, and stress scores were also associated with less income, performance concerns, severe injury history, and inadequate social support. Conclusion: MH problems in referees were associated with a wide range of variables including younger age, being single, refereeing at lower-levels, performance concerns, and inadequate social support. In light of these results, MH assessments should be undertaken with referees to detect which officials are at greater risk of MH problems. Doing so will help to enable appropriate and timely MH interventions.